The Influence of Good Corporate Governance, Intellectual Capital on Intellectual Capital Disclosure with Financial Performance as an Intervening Variable - Lina Hadiputranti SOEHARNO; Apollo DAITO (International Journal of Environmental, Sustainability, and Social Science, 2024)
The objective to be achieved in this study is to test how the influence of Good Corporate Governance, Intellectual Capital on Intellectual Capital Disclosure with Financial Performance as an Intervening Variable. The population in this study is high-tech manufacturing companies listed on the Indonesia Stock Exchange. The research data was taken from the Indonesia Stock Exchange website for the period 2017 - 2019. The research method used is causal research, with multiple linear regression analysis methods. The sampling technique used purposive sampling and the data analysis technique used E-Views 11. The results of the study showed that (1) Good Corporate Governance, which is proxied by Institutional Ownership, the Proportion of Independent Audit Committees has a significant positive effect on Intellectual Capital Disclosure, (2) Good Corporate Governance, which is proxied by the Proportion of Independent Commissioners, does not have an effect on Intellectual Capital Disclosure, (3) Good Corporate Governance, which is proxied by Managerial Ownership and Intellectual Capital, has a significant negative effect on Intellectual Capital Disclosure, (4) Financial Performance is unable to mediate the relationship between GCG and Intellectual Capital Disclosure, Financial Performance mediates the relationship between Intellectual Capital and Intellectual Capital Disclosure.